The Impact of Digital Marketing and Product Pricing on Purchase Intention and Customer Satisfaction - Ulfitriana; Dewi, Novi Yanti Sandra; Agustina, Ahadiah; Mukhlisin (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the impact of digital marketing and pricing on consumer buying interest and customer satisfaction at three bakery shops in Mataram City: Delicious Mooik, Luna Bakery, and Mirasa Bakery. The research method used is descriptive quantitative with a survey approach. A sample of 105 respondents was taken using accidental sampling technique and analyzed using multiple linear regression with the help of SPSS software. The results showed that digital marketing contributed 30.3% to purchase intention, while pricing had a greater influence, at 54%. When combined, the effect increases to 59.8%. Digital marketing also contributed 32% to customer satisfaction, while pricing had a more dominant impact, at 49.8%. Simultaneously, these two variables influence customer satisfaction by 57.2%. Pricing has a more dominant influence than digital marketing on both dependent variables. The implications of this study indicate that bakery businesses in Mataram City need to prioritize competitive pricing strategies, such as ensuring price compatibility with product quality and benefits. On the other hand, optimizing digital marketing by utilizing social media and e-commerce platforms can increase customer interaction and brand trust, thereby supporting increased customer satisfaction and long-term loyalty. This combination of strategies is important to create sustainable competitiveness in the bakery industry.